The dove of death : a mystery of ancient Ireland - Tremayne, Peter (Tremayne, Peter. Sister Fidelma novels., 2010)
AD 670. An Irish merchant ship is attacked by a pirate vessel off the coast of the Breton peninsular. Murchad, the captain, and a prince from the kingdom of Muman, are killed in cold blood after they have surrendered. Among the other passengers who manage to escape the slaughter are Sister Fidelma of Cashel and her faithful companion, Brother Eadulf. The prince was Fidelma's cousin and she is determined to bring the killers to justice...